STRATEGI PEMBELAJARAN BAHASA ARAB DENGAN PERMAINAN TWO STAY TWO STRAY DALAM MENINGKATKAN PENGUASAAN MUFRADAT - Kusuma Wardhani, Dyah Ayu; Emiliana, Emiliana; Sirtufillaily, Sirtufillaily; Suparmanto, Suparmanto (Al-Maraji' : Jurnal Pendidikan Bahasa Arab, 2023)
Language was created for man and humanity, so it is very important for people to understand and master Arabic. Language acquisition is one aspect of acculturation and the level of acculturation of a person in certain language groups in acquiring other languages or what is meant by a second language or foreign language as a means of communication So that this two stay two stray method can be used as a method learning for the introduction and cultivation of Arabic from elementary school age